Effects of Fluorination Position on Fused‐Ring Electron Acceptors. Issue 2 (14th August 2020) - Dai, Shuixing; Zhou, Jiadong; Lau, Tsz-Ki; Rech, Jeromy James; Liu, Kuan; Xue, Peiyao; Xie, Zengqi; Lu, Xinhui; You, Wei; Zhan, Xiaowei
Abstract : Four fused‐ring electron acceptors consisting of the same indacenobis(dithieno[3, 2‐ b ;2′, 3′‐ d ]thiophene) core and 2‐(3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile end groups without or with fluorination on side chains and/or end groups are compared to probe the impacts of fluorination position on molecular packing and optical, electronic, and photovoltaic properties of the nonfullerene acceptors systematically. The fluorination on side chains blue shifts, whereas that on end groups red shifts absorption spectra. Both fluorinations downshift energy levels and enhance electron mobility. The single‐crystal data show that fluorination on side chains hardly affects the aggregate structure but induces intermolecular H‐bonding formation between side groups, leading to closer molecular stacking; fluorination on end groups induces formation of a larger π‐orbital plane, closer framework, and interpenetrating charge‐transfer pathways. While both methods of fluorinations decrease open‐circuit voltage, there is an increase in short‐circuit current density, fill factor, and power conversion efficiency (PCE) of organic solar cells. Finally, in combination with the polymer donor FTAZ, INIC4/INIC3 with fluorination on side chains or end groups yields PCEs of 9.6–11.6%, which is higher than INIC without fluorination (7.8%). FINIC with fluorination on both side chains and end groups yields the highest PCE of 13.0%. Abstract : Four fused‐ring electron acceptors consisting of the same indacenobis(dithieno[3, 2‐ b ;2′, 3′‐ d ]‐thiophene) core and 2‐(3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile end groups without or with fluorination on side chains and/or end groups are compared to probe the impacts of fluorination position on molecular packing and optical, electronic, and photovoltaic properties of the nonfullerene acceptors systematically.